Fields of blood : the Prairie Grove Campaign - Shea, William L. (Civil War America (Series), 2009)
Shea narrates the events surrounding Prairie Grove, Arkansas, one of the great unsung battles of the Civil War that effectively ended Confederate offensive operations west of the Mississippi River. The book provides a colourful account of a gruelling campaign that lasted five months and covered hundreds of miles of rugged Ozark terrain. In an analysis of the personal, geographical, and strategic elements that led to the fateful clash in northwest Arkansas, the book describes a campaign notable for rapid marching, bold movements, hard fighting, and the most remarkable raid of the Civil War.